2013
DOI: 10.1186/1752-153x-7-50
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cigarette smoke particle deposition within the Vitrocell® exposure module using quartz crystal microbalances

Abstract: BackgroundCigarette smoking is a cause of a variety of serious diseases, and to understand the toxicological impact of tobacco smoke in vitro, whole smoke exposure systems can be used. One of the main challenges of the different whole smoke exposure systems that are commercially available is that they dilute and deliver smoke in different ways, limiting/restricting the cross-comparison of biological responses. This is where dosimetry – dose quantification – can play a key role in data comparison. Quartz crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 35 publications
1
45
1
Order By: Relevance
“…QCM technology has previously been described in a set-up similar to this by Adamson et al, 2013 [17] and has been shown to correlate with particulate spectrofluorescence techniques. During the whole smoke generation and exposure phase, the QCM took mass readings every 2 seconds in real-time.…”
Section: Methodsmentioning
confidence: 99%
“…QCM technology has previously been described in a set-up similar to this by Adamson et al, 2013 [17] and has been shown to correlate with particulate spectrofluorescence techniques. During the whole smoke generation and exposure phase, the QCM took mass readings every 2 seconds in real-time.…”
Section: Methodsmentioning
confidence: 99%
“…QCM technology has been incorporated into a variety of exposure chambers [20,24,26] and has been shown to correlate strongly with particulate spectrofluorescence techniques [20]. Prior to smoke exposure, the QCM module was acclimatised for several minutes prior to the baseline being set to zero.…”
Section: Methodsmentioning
confidence: 99%
“…A quartz crystal microbalance (QCM) (Vitrocell ® Systems, Waldkirch, Germany) was included in situ of exposure at position 4 within the Ames module, distal to the smoke inlet, as previously demonstrated [38][39][40]. QCMs provide a gravimetric measure of deposited mass, providing a valuable quality control (QC) measure of smoke exposure within and between runs, and allows data to be presented as a function of deposited mass (g/cm 2 ).…”
Section: Measuring Dosementioning
confidence: 99%